FAKTOR PENENTU KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Dewi Sarifah Tullah; Erma Apriyanti; Emi Suryati (STIE Muhammadiyah Jakarta, 2020)
This study aims to examine the effect of internal control systems, Good Government Governance and Human Resources Quality on the quality of local government financial reports in the Provinces of West Java and Banten. The Unit of Analysis in this study was the local government in the provinces of West Java and Banten. The sample in this study was the Regional Financial Management Agency in the Provinces of West Java and Banten. In this study, the number of samples used was 34 samples with an error rate of 5%. Data collection techniques using a questionnaire. Methods of data analysis using validity and reliability tests, multiple linear regression data analysis, classic assumption tests (normality, multicollinearity, heteroscedasticity), t tests, and coefficient of determination analysis (R2). The results of this study indicate that the internal control system and Human Resources Quality do not have a significant effect on the quality of local government financial reports, while Good Government Governance affects the quality of local government financial reports.